KONSEP JNANA YAJNA DALAM KAKAWIN SUTASOMA - Heri Purwanto; Coleta Palupi Titasari (UHN IGB Sugriwa Denpasar, 2023)
This study to reveal the concept of jnana yajna contained in the Kakawin Sutasoma text. The primary data used for this research is Kakawin Sutasoma which has been translated by Mastuti and Brahmantyo (2019). Primary data is studied by using textual analysis, then in interpretating its meaning assisted by supporting sources (archaeological data). Based on the results of this study, it shows that the presentation of knowledge can be done by teaching and learning in an educational place called the mandala kadewaguruan. Places where education is located on the slopes of mountains, valleys, rivers, and hills. As Sang Sutasoma sought knowledge on Mount Agung (Semeru), who eventually became a teasher and taught various sacred teachings